Heavy metal ions removal from aqueous solution by xanthate-modified cross-linked magnetic chitosan/poly(vinyl alcohol) particles. Issue 45 (26th May 2017) - Lv, Long; Chen, Nan; Feng, Chuanping; Zhang, Jing; Li, Miao
Abstract : Xanthate-modified cross-linked magnetic chitosan/poly(vinyl alcohol) particles (XCMCP) were synthesized and applied to remove Pb(ii ) and Cu(ii ) ions from aqueous solutions. Abstract : Xanthate-modified cross-linked magnetic chitosan/poly(vinyl alcohol) particles (XCMCP) were synthesized and applied to remove Pb(ii ) and Cu(ii ) ions from aqueous solutions. To further explore the adsorption mechanisms, the complexes were characterized by Fourier transform infrared spectroscopy (FTIR), Scanning Electron Microscope (SEM), Vibrating Sample Magnetometer (VSM), X-ray Diffraction (XRD), and X-ray Photoelectron Spectroscopy (XPS). The effects of pH, contact time, and temperature on the adsorption process were investigated. The results showed that the particles were super-paramagnetic with a saturation magnetization of 34.8 emu g −1, had an irregular surface, and successfully introduced xanthate groups. The adsorption capacity of XCMCP for Pb(ii ) or Cu(ii ) was better in near-neutral pH. The kinetic data were well-described by the pseudo-second-order kinetic model. The Langmuir and Freundlich isotherms fit the equilibrium data well. Based on the Langmuir isotherm model, the maximum adsorption capacities of XCMCP at 328 K were 59.855 and 139.797 mg g −1 for Pb(ii ) and Cu(ii ), respectively. Meanwhile, the effect of temperature on the reaction process was not significant. XCMCP exhibited a good property for repeated use and could still retain an effective adsorption efficiency after seven cycles. The mechanism for Pb(ii ) and Cu(ii ) adsorption onto XCMCP involves the interactions of N and S atoms with heavy metals, crystal formation and surface adsorption. Thereinto, contributions of crystal formation were dominant. These properties of XCMCP make it promising for practical use, which suggests that XCMCP is a promising adsorbent for hazardous-metal-ion-contaminated water treatment.